(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article studies the experience of the United States of America in attracting foreign investments to the Republic of Uzbekistan and, in order to understand more deeply the significance of this experience for improving Uzbekistan’s investment climate, the U.S. investment position is analysed from statistical, economic and financial perspectives. The article analyses the successful U.S. strategies in the field of investment and, on the basis of statistical and practical data, recommends promising directions that can be implemented in Uzbekistan.